Reproductive outcomes, including neonatal data, following sperm injection in men with obstructive and nonobstructive azoospermia: case series and systematic review (Clinics, 2013)
We compared pregnancy outcomes following intracytoplasmic sperm injection for the treatment of male infertility according to the type of azoospermia. First, we analyzed our data from 370 couples who underwent intracytoplasmic sperm injection using sperm from men with obstructive azoospermia and nonobstructive azoospermia, and the outcomes were compared to a group of 465 non-azoospermic infertile males. Then, we performed a systematic review of the published data on pregnancy and neonatal outcomes of children born after sperm injection using sperm from men with obstructive and nonobstructive azoospermia. Live birth rates were significantly lower in the nonobstructive azoospermia group (21.4%) compared with the obstructive azoospermia (37.5%) and ejaculated sperm (32.3%) groups. A total of 326 live births resulted in 427 babies born. Differences were not observed between the groups in gestational age, preterm birth, birth weight and low birth weight, although we noted a tendency towards poorer neonatal outcomes in the azoospermia categories. The overall perinatal death and malformation rates were 2.8% and 1.6%, respectively, and the results did not differ between the groups. We identified 20 published studies that directly compared pregnancy outcomes between obstructive azoospermia and nonobstructive azoospermia. Most of these studies were not designed to detect differences in live birth rates and had lower power to detect differences in less frequent outcomes, and the reporting of neonatal outcomes was unusual. The included studies reported either a decrease or no difference in pregnancy outcomes with intracytoplasmic sperm injection in cases of nonobstructive azoospermia and obstructive azoospermia. In general, no major differences were noted in short-term neonatal outcomes and congenital malformation rates between children from fathers with nonobstructive azoospermia and obstructive azoospermia.